Peran Ekstrakulikuler dalam Meningkatkan Kreatifitas Siswa MAN 1 Pangandaran - Risalatun Nisa; Alfiyatun Alfiyatun; Imas Patmawati (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2024)
The creativity in each student needs to be developed and honed to be more trined. As a teacher, you must know the talents of the students. This makes it easier for teachers to place them according to their expertise. The need for support from schools in the form of facilities that support these extracurricular activies. There are still many schools that do not support extracurricular activies either form the coaches, funds, and facilities. This type of research is increasing persistence as a provision for researchers to be able to increase perseverance by reading various reference books and research results.